Anti-Alzheimer's Potency of Rich Phenylethanoid Glycosides Extract from Marrubium vulgare L.: In Vitro and In Silico Studies - Mahmoud Emam; Samah A. El-Newary; Hanan Y. Aati; Bin Wei; Mohamed Seif; Abeer Y. Ibrahim (MDPI AG, 2024)
Background/Objectives: Marrubium vulgare L. (M. vulgare), the white horehound, is well known for treating inflammation-related diseases. Methods: In this context, we investigated the efficacy of M. vulgare ingredients in treating Alzheimer's disease using various in vitro and in silico antioxidant, anti-inflammatory, anti-cholinesterase, and anti-tyrosinase mechanisms. Results: In our results, sixty-one components were tentatively identified using gas and liquid chromatography (GC-MS and LC-MSn) and categorized as hydrocarbons, fatty acids, and polyphenolics. The extract inhibited linoleic oxidation with an IC50 value of 114.72 µg/mL, captured iron (Fe2+) ions with an IC50 value of 164.19 µg/mL, and displayed reducing power. In addition, the extract showed radical-scavenging ability towards DPPH•, NO•, ABTS•+, and H2O2 assays compared to L-ascorbic acid and butylated hydroxytoluene. The DPPH• was scavenged by 77.62% at 100 µg/mL, and NO•, ABTS•+, and H2O2 were scavenged with IC50 values of 531.66, 117.51, and 143.10 µg/mL, respectively. M. vulgare also exhibited discriminating anti-inflammatory potency against cyclooxygenase (COX-2) with IC50 values of 619.15 µg/mL compared to celecoxib (p > 0.05). Notably, three Alzheimer's biomarkers, acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and tyrosinase were significantly inhibited. The molecular docking study supposed that the phenylethanoid glycosides of samioside and forsythoside B inhibited AChE and tyrosinase enzymes with low binding affinities of −9.969 and −8.804 kcal/mol, respectively. Marruboside was a proper inhibitor of COX and BChE enzymes with a binding score of −10.218 and −10.306 kcal/mol, respectively. Conclusions: M. vulgare extract showed significant inhibitory actions, which suggest that it could have a promising potential as an anti-Alzheimer agent.